Serous Cavity Fluid and Cerebrospinal Fluid Cytopathology - Ali, Syed Z.; Cibas, Edmund S. (Essentials in Cytopathology, 2012)
Cytologic diagnosis by examination of exfoliated cells in serous cavity fluids is one of the most challenging areas in clinical cytopathology. Almost 20% of the effusions examined are directly or indirectly related to the presence of malignant disease, with carcinoma of the lung as the most common underlying culprit.  This volume published in the Essentials in Cytopathology book series will fulfill the need for an easy-to-use and authoritative synopsis of site specific topics in cytopathology. .